A case of successful surgical treatment of extragenital endometriosis - Dresvyanskaya T. V.; Prusov I. A; Fokina A. P.; Bichurin R. A.; Nadich V. E.; Pozdnyakova O. F.; Oshueva S. V.; Nikitenko I. A.; Safronova N. I; Serova E. V. (LCC «Medicine-Inform», 2018)
A case of successful surgical treatment of extragenital endometriosis Dresvyanskaya T. V.1, Prusov I. A.1, Fokina A. P.1, Bichurin R. A.1, 2, Nadich V. E.1, Pozdnyakova O. F.1, Oshueva S. V.1,  Nikitenko I. A.1, Safronova N. I.1, Serova E. V.1, 2 1Krasnoyarsk Interdistrict Clinical Hospital № 4 2Krasnoyarsk State Medical University named after Prof. V. F. Voyno-Yasenetskiy Extragenital endometriosis (EGE) is the most rare variant of endometriosis, characterized by the proliferation of tissue that is similar in morphology and function to the endometrium, in organs and tissues that are not related to the reproductive system. The frequency of EGE is 6-8% of all cases of endometriosis. The frequency of detection of endometriosis is increasing in recent years. The cases described in the publications are non-standard, manifestations of the disease are erased or similar to other diseases. Patients with EGE are often treated in non-specialized departments, which leads to the errors in the tactics of treatment. The correct diagnosis is often established during the operation and is confirmed by the results of histological examination, and treatment often requires the involvement of specialists from other areas. In this article, there is a case of successful surgical treatment of EGE of rare localization. In the surgical treatment of endometriosis, as well as in other surgical interventions associated with the opening of the uterine cavity (for example, caesarean section), a specialist should be aware of the possibility of implantation of endometrioid heterotopies and avoid contact of the endometrium or tissues of endometriosis with the peritoneum and operating wound. Key words: extragenital endometriosis, surgical treatment, endometrium, implantation theory. For citation: Dresvyanskaya T.V., Prusov I.A., Fokina A.P. et al. A case of successful surgical treatment of extragenital endometriosis // RMJ. 2018. № 2(I). P. 70-72.